Impact of pore size of ordered mesoporous carbon FDU-15-supported platinum catalysts on oxygen reduction reaction. (2nd February 2017) - Zhao, Gang; Zhao, T.S.; Xu, Jianbo; Lin, Zeng; Yan, Xiaohui
Abstract: To investigate the impact of pore size of ordered mesoporous carbon (OMC) FDU-15-supported Platinum (Pt) catalysts on oxygen reduction reaction (ORR), OMC FDU-15 with various pore sizes ranging from 4.0 nm to 8.1 nm are synthesized through a soft-template method, and then FDU-15-supported Pt catalysts are prepared by chemical impregnation method. Characterizations show that increase in pore size enlarges the specific surface area and the pore volume of FDU-15, but decreases the electrical conductivity. Particle size of FDU-15-supported Pt catalyst is also influenced in a decreasing trend with the increase of pore size. Electrochemical measurement demonstrates that FDU-15-supported Pt catalyst with a pore size of 6.5 nm yields the highest electrocatalytic activity for ORR, which is further confirmed by single cell test on DMFC, as the catalyst for cathode. Highlights: FDU-15 carbons with different pore sizes are prepared. Pt catalysts supported on FDU-15 carbons are prepared. Influence of pore size on ORR is investigated. Pt catalyst with a pore size of 6.5 nm yields the best performance.